Digital divide: a phenomenon of unequal adoption of technology by SMMEs in the agribusiness sector in South Africa - Blessing Mbatha (Communicare)
The digital evolution and the adoption of technology have made it possible for information access and management to improve the social and economic impacts of the tourism sector globally. Technology has undoubtedly become the prime driver of modern e-commerce. This article examines the digital divide as a barrier to the adoption of technology by small, medium, and micro enterprises (SMMEs) in the agribusiness sector in the city of Tshwane, South Africa. The study adopted a quantitative approach and data were collected through a self-administered questionnaire. The data were subsequently analysed by using descriptive statistics. The relationships between variables were compared and interpretations were made. The results showed that a digital divide is hampering the adoption of technology by SMMEs in the agribusiness sector. The results further revealed that the high cost of technology/online platforms, limited funds and a lack of technical know-how are some of the obstacles faced by SMMEs in the adoption of information and communication technologies. However, the study also established that if these obstacles could be addressed, the benefits would be substantial. It is concluded that empirical work is required to investigate the extent to which SMMEs in South Africa are adapting to the challenges posed by the digital divide.